Human to animal transmission of influenza A(H1N1)pdm09 in a turkey breeder flock in Norway. Issue 1 (1st January 2017) - Kulberg Sjurseth, Siri; Gjerset, Britt; Bragstad, Karoline; Hungnes, Olav; Wisløff, Helene; Er, Chiek; Valheim, Mette; Løtvedt, Siri M.; David, Bruce; Hanssen, Skjalg A.; Hauge, Siri H.; Hofshagen, Merete
ABSTRACT: Introduction : Routine surveillance samples disclosed seropositivity to influenza A virus (IAV) in a Norwegian turkey breeder flock. Simultaneous reports of influenza-like symptoms in farm workers and a laboratory confirmed influenza A(H1N1)pdm09 (H1N1pdm09) infection in one person led to the suspicion of a H1N1pdm09 infection in the turkeys. Animals and methods : H1N1pdm09 infection was confirmed by a positive haemaggutinin inhibition test using H1N1pdm09 antigens, and detection of H1N1pdm09 nucleic acid in reproductive organs of turkey hens. The flock showed no clinical signs except for a temporary drop in egg production. Previous reports of H1N1pdm09 infection in turkeys suggested human-to-turkey transmission (anthroponosis) during artificial insemination. Results and discussion : The flock remained seropositive to IAV and the homologous H1N1pdm09 antigen throughout the following 106 days, with decreasing seroprevalence over time. IAV was not detected in fertilised eggs or in turkey poults from the farm, however, maternally derived antibodies against H1N1pdm09 were found in egg yolks and in day-old poults. Genetic analyses of haemagglutinin gene sequences from one of the infected farm workers and turkeys revealed a close phylogenetic relationship, and confirmed human-to-turkey virus transmission.